2018
DOI: 10.1364/oe.26.029460
|View full text |Cite
|
Sign up to set email alerts
|

Millijoule femtosecond pulses at 1937 nm from a diode-pumped ring cavity Tm:YAP regenerative amplifier

Abstract: We present an infrared source operating at 1937 nm center wavelength capable of generating 1.35 mJ pulse energies with 1 kHz repetition rate and 2 GW peak power based on a diode-pumped Tm:YAP regenerative amplifier. The obtained pulses after 45 round trips have been compressed down to 360 fs. Using only a small portion (15 µJ) of the output of the system we managed to generate a white light continuum in a 3 mm YAG window that exhibits the viability of the system as a suitable candidate for a pumping source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…A wide variety of optical modulators are used in laser applications [1][2][3][4][5][6][7]. However, only modulators based on electro-optic and acousto-optic principles are used for high power laser system applications.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of optical modulators are used in laser applications [1][2][3][4][5][6][7]. However, only modulators based on electro-optic and acousto-optic principles are used for high power laser system applications.…”
Section: Introductionmentioning
confidence: 99%
“…The 1937-nm pump pulses used in our scheme were derived from an updated version of the Tm:YAP regenerative amplifier [48], operating under a 10-kHz repetition rate. Figure 1 depicts the schematic of the experimental setup.…”
Section: Methodsmentioning
confidence: 99%
“…The regenerative amplifier was capable of providing 0.122 mJ of pulse energy with a 360-fs pulse duration after 45 round trips, at a crystal temperature of −20 • C. The regenerative amplifier chamber was purged with nitrogen to reduce the effect of absorption from the water molecules [48,49]. The output pulses of the amplifier were recorded with a resolution of 0.04 nm using a spectrum analyzer (Yokogawa-AQ6375 by Yokogawa Meters & Instruments Corporation, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The key parts in the CPA system include pulse stretcher, laser amplifier and pulse compressor. Due to the wavelength of 2 µm far beyond most standard commercialized fiber zero-dispersion wavelength (ZDW), such as standard single-mode fibers (SMF) and fluoride fibers, and normally in their anomalous dispersion region; the most reported 2 µm CPA systems adopted the stretchers are mainly the traditional bulk grating configuration such as Offner-type stretcher, Martinez-type stretcher and chirped volume Bragg grating (CVBG) stretcher [20][21][22][23]. In 2016, C. Gaida et al demonstrated a 2 µm CPA system, in which the seed pulses were stretched in an Offner-type stretcher to 1 ns, and the power was amplified to 35.8 W [20].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, C. Gaida et al demonstrated a 2 µm CPA system, in which the seed pulses were stretched in an Offner-type stretcher to 1 ns, and the power was amplified to 35.8 W [20]. In 2018, S. A. Rezvani et al used a Martinez-type stretcher in a Tm:YAG crystal based regenerative amplifier, in which the pulse duration was stretched to 100 ps [21]. In 2020, J. Huang et al stretched the 3 μm pulse duration from 126 fs to 13 ps by using a Martinez-type stretcher in an Er: ZBLAN fiber-based nonlinear CPA system [22].…”
Section: Introductionmentioning
confidence: 99%